Equalizing educational opportunity through educational finance reform - John Roemer; Julian R. Betts (University of California, Department of Economics, 1999)
We analyze the reallocations of educational expenditures required to equalize opportunities, according to the theory of Roemer (1998). Using the NLSYM data set, we find that implementing an equal-opportunity policy across men of different races, by using educational finance as the instrument, and holding per capita educational finance fixed, would require spending six to ten times as much on black students, per capita, as on white students. Implementing an equal-opportunity policy across men from different socio-economic backgrounds, but ignoring race, does almost nothing to equalize opportunities for men of different races. Raising the school-leaving age by one year, as opposed to increasing spending per pupil directly, is a relatively inexpensive way of reducing inequality of opportunity across races, but the reduction in opportunity inequality it achieves is very small.
Keywords: D53; I22; I28; 330; Equal Opportunity; Educational Finance; School Quality